1998
DOI: 10.1006/exer.1998.0546
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of the Inner and Outer Blood Retinal Barrier in Streptozotocin-Induced Diabetes

Abstract: Using vitreous fluorophotometry and quantitative fluorescence microscopy the authors studied the permeability of the blood-retinal barrier (BRB) to fluorescein in control and in 8 days streptozotocin-induced diabetic rats. Vitreous fluorophotometry showed that fluorescein permeates BRB in control and in diabetic rats. However, in diabetic rats the permeability to fluorescein was significantly increased as compared to control rats. The vitreous penetration ratio (VPR) values for total and free fluorescein at 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 9 publications
3
61
0
3
Order By: Relevance
“…The main cause for this increase could be the breakdown of the blood-retinal barrier, especially the inner one, and the subsequent edematous swelling, in agreement with other studies [15,16,17]. Therefore, a gradual decrease in the thickness of the inner retina, to well below that observed in the normal state, seems likely to arise from the decay of the neural components affected by the altered biochemical environment, including the glucose transport system [18,19].…”
Section: Discussionsupporting
confidence: 85%
“…The main cause for this increase could be the breakdown of the blood-retinal barrier, especially the inner one, and the subsequent edematous swelling, in agreement with other studies [15,16,17]. Therefore, a gradual decrease in the thickness of the inner retina, to well below that observed in the normal state, seems likely to arise from the decay of the neural components affected by the altered biochemical environment, including the glucose transport system [18,19].…”
Section: Discussionsupporting
confidence: 85%
“…activator protein-1 have been shown to be partially responsible for MCP-1 regulation . Previous studies have demonstrated that oxidized LDL and glycoxidized LDL are potent inducers of NF-kB activation in vascular cells and monocyte/macrophages (Do carmo et al 1998, Sonoki et al 2002. Moreover, the results from electrophoretic mobility shift assay and chromatin immunoprecipitation assays showed that oxidized glycated LDL and oxidized LDL induced MCP-1 expression via NF-kB activation.…”
Section: Discussionmentioning
confidence: 92%
“…What is apparent is that the multifactorial disruption of inner and outer blood-retinal barriers leads to abnormal inflow of fluid into the neurosensory retina exceeding the outflow, ending up with intraretinal and subretinal fluid accumulation. [1][2][3][4] Besides making the objective diagnosis and quantitative evaluation of macular oedema possible, optical coherence tomography (OCT) offers the opportunity to assess in vivo histologic cross-sections of the healthy and diseased retina, leading to a better understanding of pathologic processes. 5,6 Three different morphologic subtypes of macular oedema were defined according to OCT: 7,8 Sponge-like diffuse retinal thickening (DRT), cystoid macular oedema (CMO) and serous retinal detachment (SRD).…”
Section: Introductionmentioning
confidence: 99%